Analysis of Operational Costs in Determining The Revenue of PT.Surya Trans Cemerlang Karawang - Pridhi, Adiilah Eka; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (West Science Business and Management, 2024)
The research is aimed at analyzing the operating costs in determining the company's revenue on PT. Surya Trans Cemerlang Karawang. Operating costs are one of the important factors that can determine the revenue of this research company using quantitative descriptive methods. The data used is secondary data from the financial report of PT. Trans Brilliant Solar Karawang for the period 2021-2023. The results of the research showed that the operating costs of P. Trans brilliant solar from 2021 to 2023 noted significant fluctuations in several major cost categories. The fall in employee salaries and office operating expenditure, as well as rising road cash costs and spare part expenditures, are key factors in the fluctuations. Nevertheless, the ratio of operating costs to company revenues is relatively stable in the range of 0.53 to 0.63%. This analysis provides an understanding of the company's operational efficiency relative to the income generated, helping in long-term financial planning and strategic decision-making. Despite fluctuations, the company managed to maintain a balance between cost and revenue, demonstrating a commitment to optimum efficiency and operational sustainability. Implications of this analysis show the company's efforts to improve operational efficiency while remaining responsive to market fluctuations, enabling for the development of more effective long-term financial strategies and commitment to compliance with relevant policies and standards, which underlie the basis for sustained operational survival and future growth.